Reduction of waste biosolids by RAS-ozonation: Model validation and sensitivity analysis for biosolids reduction and nitrification. (March 2015) - Isazadeh, Siavash; Urbina Rivas, Luis Enrique; Ozdural Ozcer, Pinar; Frigon, Dominic
Abstract: Biosolids reduction model by return activated sludge ozonation was validated by simulating nitrification data compiled from our pilot-scale and the literature studies. Then, a global sensitivity analysis (GSA) was performed to identify influential and non-influential parameters for biosolids reduction efficiency, change in specific nitrification activity (SNA), and alteration to expected nitrification stability. In general, the model outputs were sensitive to operational and ozone reaction parameters, but not to biochemical parameters. For operational parameters, mainly temperature and initial solids retention time (SRT) influenced all model outputs. For biosolids reduction, increase in the degradability of the influent COD decreased the reduction efficiency. For SNA, the changes were highly dependent on the influent TKN/COD ratio. Our findings also imply that the stability of the nitrification process in ozonated systems should be enhanced at constant MLVSS for warm temperatures, but could be reduced at temperatures below 12 °C and aerated SRTs below 10 days. Graphical abstract: Highlights: Model predicts biosolids reductions and nitrification rates in 2 different years. Initial SRT and temperature influenced most biosolids reduction by ozonation. Model explains how nitrification can both increase and decrease due to ozonation. Nitrifiers' inactivation rate is higher than non-degradable VSS transformation rate. RAS-ozonation could decrease the stability of nitrification at temperatures <12 °C.